Prevalence of obstructive sleep apnea syndrome in hospitalized patients with type 2 diabetes in Beijing, China. Issue 11 (2nd July 2022) - Ding, Shan; Zhang, Puhong; Wang, Li; Wang, Du; Sun, Kaige; Ma, Yahui; Wang, Hongbing; Xu, Chun; Zhang, Rui; Zhang, Xianbo; Wang, Hongyu; Zhao, Fang; et al.
Abstract: Aims/Introduction: To estimate the prevalence, and patient clinical and demographic profile, as well as risk factors associated with obstructive sleep apnea syndrome (OSAS) in hospitalized patients with type 2 diabetes mellitus in Beijing, China. Materials and Methods: Hospitalized adult patients with type 2 diabetes mellitus were consecutively screened and invited for an overnight polysomnography from four hospitals in Beijing, China, from May 2016 to February 2017. We used the American Academy of Sleep Medicine 2012 polysomnography recording techniques and scoring criteria to identify the type of apnea and the severity of OSAS. The χ 2 ‐test was used to evaluate differences between groups regarding the prevalence, and demographic and other clinical parameters. Results: A total of 735 patients were found eligible for the study, of whom 309 patients completed the overnight polysomnography. The mean age of the patients was 58.2 ± 10.9 years, and most (67.3%) were men. The prevalence of overall (apnea hypopnea index ≥5/h), moderate‐to‐severe (apnea hypopnea index ≥15/h) and severe (apnea hypopnea index ≥30/h) OSAS was 66.3% (95% confidence interval 60.8–71.6%), 35.6% (95% confidence interval 30.3–41.2%) and 16.5% (95% confidence interval 12.5–21.1%), respectively. Central and mixed apnea contributed 12% to all sleep‐disordered breathing. With the aggravation of OSAS, the combined prevalence for central, mixed and obstructive apnea increased from 57% to 70%. We found OSAS to be associated with older age, obesity, self‐reported snoring and apnea, and diabetes complications. Conclusions: Guidelines on screening and treatment of OSAS among hospitalized patients with diabetes are needed to direct the routine practice for diabetes endocrinologists for optimal clinical care of such patients. Abstract : Two thirds of T2DM patients are suffering from OSAS, and half of them are moderate to severe. The aggravation of OSAS is positively related to increased apnoea and severe nocturnal hypoxemia. We strongly suggest developing strategies and pathways for endocrinologists to conduct OSAS screening, diagnosis and treatment during their routine practice.